Effects of bismuth and nickel on physico-chemical and catalytic properties of vanadium phosphorus oxide catalyst - Yuen, Choon Seon (2012)
Vanadium phosphorus oxide (VPO) catalysts in this study was synthesized by using dihydrate or VPD method which involved two steps of preparation. The first step is the preparation of dihydrate, VOPO4⋅2H2O by using V2O5 reacting with aqueous o-H3PO4 in distilled water. For the second step, the preparation of precursor,hemihydrate VOHPO4⋅0.5H2O is synthesized by reacting, VOPO4⋅2H2O with isobutanol. For promoted VPO precursor, Bi or Ni salt were added in the mixture of VOPO4⋅2H2O and isobutanol. For milled unpromoted and promoted precursors, theywere milled for 1 hour with ethanol as medium. The precursors produced were calcined in a flow of n-butane/air mixture. The catalysts obtained were confirmed as (VO)2P2O7 phase by X-ray Diffraction (XRD). The catalysts were characterized by Brunauer-Emmett-Teller (BET) surface area measurement, inductively coupled plasma-atomic emission spectroscopy (ICP-AES), scanning electron microscopy (SEM) and temperature programmed reduction in H2 (H2-TPR) techniques. The catalytic properties of the synthesized catalysts were carried out by using an fixed bed microreactor. All catalysts gave main peaks at 2θ=22.9°, 28.5° and 30.0° which correspond to (020), (204) and (221) reflections of pyrophosphate phase respectively. The incorporation of Bi and Ni promoters (in mole ratio) into the VPO catalyst enhanced the surface area of the synthesized catalysts. SEM micrographs clearly revealed that the formation of more isolated platelets and more prominent plate-like crystallite that was arranged into the characteristic of rosette cluster. On the other hand, the reactivity of the oxygen species linked to V5+ and V4+ was investigated in the unpromoted and promoted catalysts by using H2-TPR, which also affected the catalytic performance of the catalyst. The results showed that promoted VPO catalysts remarkably lowered the temperature of the reduction peak associated with V5+. This V5+ led to the enhancement of the n-butane activation and improvement of the selectivity to the maleic anhydride. Moreover, the TPR profile also showed that promoted VPO catalysts possesses higher amount of active oxygen species associated with V4+. It meant that promoted VPO catalysts possesses higher amount of V4+-O- pair, which eventually caused a higher conversion rate in the selective oxidation of n-butane to maleic anhydride. Besides, the mechanochemical treatment successfully reduced the crystallite size of the catalysts and consequently increased their surface area, especially promoted milled catalysts. TPR results demonstrated that both reduction peaks for each mechanochemical treatment catalyst shifted from the maxima reduction peak to lower temperature. It then improved the amount of oxygen species removed from the catalysts. Furthermore, the milled catalysts have shown better catalytic performance than unmilled catalysts. Addition of promoters for milled catalysts were shown to enhance the activity and the selectivity of n-butane. CatBi1Ni1M has the highest n-butane conversion (60%) and selectivity to maleic anhydride (42%), while CatUnpromotedM has only 41% conversion and 29% selectivity to maleic anhydride. Besides, promoted unmilled catalysts were also shown to increase the activity and selectivity of n-butane. CatBi1Ni1 gave an n-butane conversion of 52% and selectivity of 39%, while CatUnpromoted gave n-butane conversion 38% and selectivity of 28%.